2019
DOI: 10.24815/jdm.v6i2.14104
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Koneksi Matematis Siswa Ditinjau dari Kemampuan Awal dan Gender

Abstract: This research aimed to examine student’s mathematical connection ability based on previous ability and gender. The instruments of the study were the researcher as the main instrument, the test of prior knowledge, the test of connection ability, interview and documentation. The triangulation technique was used for the data (test, observation, interview, and documentation). The subject of this research were six students representing each category of the previous ability. Three indicators of mathematical connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
1
8
0
4
Order By: Relevance
“…From the results of the analysis of the two subjects in the high MR category, it was found that female students were superior to boys, but the difference was only slightly where male students were less than perfect in the MCA indicator linking mathematics in their field due to forgetting the speed formula but he knew this question relates to other fields. This is following the research conducted by Aliyah et al, (2019) which found that female students got better test scores than boys. Eliza (2020) also revealed that men are better at reasoning, relying only on their memory, and lacking in literacy while women are better at learning styles where women are more diligent, thorough, and careful in learning and like to read, this is what makes women more attractive.…”
Section: Subjects With Medium Mrsupporting
confidence: 66%
“…From the results of the analysis of the two subjects in the high MR category, it was found that female students were superior to boys, but the difference was only slightly where male students were less than perfect in the MCA indicator linking mathematics in their field due to forgetting the speed formula but he knew this question relates to other fields. This is following the research conducted by Aliyah et al, (2019) which found that female students got better test scores than boys. Eliza (2020) also revealed that men are better at reasoning, relying only on their memory, and lacking in literacy while women are better at learning styles where women are more diligent, thorough, and careful in learning and like to read, this is what makes women more attractive.…”
Section: Subjects With Medium Mrsupporting
confidence: 66%
“…Matematika merupakan aset yang sangat penting bagi siswa sekolah dasar dan menengah karena mendorong perkembangan intelektual secara positif untuk menyongsong perubahan yang semakin maju. Musriliani (Musriliani, 2015) Menurut peneliti, konsep belajar matematika adalah belajar angka dan angka yang prosesnya melalui perhitungan dan memiliki hasil tertentu, dan hasilnya tidak dapat dituliskan.…”
Section: Pendahuluanunclassified
“…Adapun indikator koneksi matematis yang diukur dalam penelitian ini (Latipah & Afriansyah, 2018;Aliyah, Yuhana, & Santosa, 2019;Indriani & Sritresna, 2022), yaitu: a) Mengidentifikasi masalah dalam kehidupan sehari-hari; b) Menggunakan konsep matematika yang terkait dengan topik yang dipelajari; c) Menggunakan konsep matematika yang berhubungan dengan disiplin ilmu lain.…”
Section: Pendahuluanunclassified